Alteration of N‐glycan profiles in patients with chronic hepatitis and hepatocellular carcinoma. Issue 9 (13th January 2015) - Miyahara, Koji; Nouso, Kazuhiro; Dohi, Chihiro; Morimoto, Yuki; Kinugasa, Hideaki; Wada, Nozomu; Takeuchi, Yasuto; Kuwaki, Kenji; Onishi, Hideki; Ikeda, Fusao; Miyake, Yasuhiro; Nakamura, Shinichiro; et al.
<x xml:space="preserve">Abstract</x> Aim Most of the modification of N‐glycosylation reported in cancers including hepatocellular carcinoma (HCC) were based on the examinations of a small number of patients or particular proteins. The aim of this study is to reveal changes in whole serum N‐glycan profiles systematically during the process of hepatocarcinogenesis and to elucidate their clinical application. Methods We analyzed sera from 105 patients with chronic hepatitis/liver cirrhosis (CH/LC) and age‐/sex‐matched healthy volunteers (HLT), as well as from 114 patients with HCC. Serum N‐glycan profiles were measured comprehensively by a new, quantitative, high‐throughput method and compared with clinical parameters. Results The total amount of N‐glycan expression was significantly higher in patients with CH/LC than in HLT; however, no differences were observed between CH/LC and HCC patients. In HCC patients, multi‐antennary glycans with fucose residues, particularly m/z 3195, were increased compared with CH/LC patients. The expression of m/z 3195 was high, especially in patients with a high number of intrahepatic lesions (>3), large tumor size (>3 cm), macroscopic vascular invasion or metastasis. The ratio of pairs of glycans on the same path of the biosynthesis pathway (m/z 3195/1914) showed a higher area under the receiver–operator curve of 0.810 than any other single glycan to distinguish HCC from CH/LC. Conclusion We demonstrate the full spectrum of the alterations of serum N‐glycans comprehensively in patients with liver disease, and elucidate the possible use of glycans as novel biomarkers of liver disease progression.